Emerging drugs and vaccines for Candidemia. Issue 12 (8th October 2014) - Moriyama, Brad; Gordon, Lori A.; McCarthy, Matthew; Henning, Stacey A.; Walsh, Thomas J.; Penzak, Scott R.
Summary Candidemia and other forms of invasive candidiasis are important causes of morbidity and mortality. The evolving challenge of antimicrobial resistance among fungal pathogens continues to highlight the need for potent, new antifungal agents. MEDLINE, EMBASE, Scopus and Web of Science searches (up to January 2014) of the English‐language literature were performed with the keywords 'Candida' or 'Candidemia' or 'Candidiasis' and terms describing investigational drugs with activity against Candida spp. Conference abstracts and the bibliographies of pertinent articles were also reviewed for relevant reports. ClinicalTrials.gov was searched for relevant clinical trials. Currently available antifungal agents for the treatment of candidemia are summarised. Investigational antifungal agents with potential activity against Candida bloodstream infections and other forms of invasive candidiasis and vaccines for prevention of Candida infections are also reviewed as are selected antifungal agents no longer in development. Antifungal agents currently in clinical trials include isavuconazole, albaconazole, SCY‐078, VT‐1161 and T‐2307. Further data are needed to determine the role of these compounds in the treatment of candidemia and other forms of invasive candidiasis. The progressive reduction in antimicrobial drug development may result in a decline in antifungal drug discovery. Still, there remains a critical need for new antifungal agents to treat and prevent invasive candidiasis and other life‐threatening mycoses.